The “Mixing” of Implant Systems - Baumgart, F. (Veterinary and Comparative Orthopaedics and Traumatology, 1991)
The so-called “mixing” of implants and instruments from different producers entertain certain risks.The use of standardized implant materials (e.g. stainless steel ISO 5832/1) from different producers is necessary but is not sufficient to justify the use of an osteosynthesis plate from one source and a bone screw from another.The design, dimensions, tolerances, manufacturing procedure, quality controls, and application technique of the instruments and implants also vary according to make. This can lead to damage, failure or fracture of the biomechanical system called “osteosynthesis” and hence the failure of the treatment undertaken. In the end, it is the patient who pays for these problems.Some examples also illustrate the potential problems for the staff and institutions involved.The use of a unique, consistent, well-tested, and approved set of implants and instruments is to be strongly recommended to avoid any additional risk.
Keywords: Osteosynthesis; mixing; liability; implants